2013
DOI: 10.1158/1078-0432.ccr-12-3039
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Estrogen Receptor-α Is Associated with Epithelial–Mesenchymal Transition and PI3K Alterations in Endometrial Carcinoma

Abstract: Purpose: We hypothesized that estrogen receptor-a (ER-a) status in endometrial carcinomas, associated with poor prognosis, is reflected in transcriptional signatures suggesting targets for new therapy.Experimental Design: Endometrial carcinoma samples in a primary investigation cohort (n ¼ 76) and three independent validation cohorts (n ¼ 155/286/111) were analyzed through integrated molecular profiling. Biomarkers were assessed by immunohistochemistry (IHC), DNA oligonucleotide microarray, quantitative PCR (q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 54 publications
7
124
1
1
Order By: Relevance
“…no. G4112F), according to the manufacturer's instructions (www.agilent.com) and described earlier (37). Arrays were scanned using the Agilent Microarray Scanner Bundle.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…no. G4112F), according to the manufacturer's instructions (www.agilent.com) and described earlier (37). Arrays were scanned using the Agilent Microarray Scanner Bundle.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…A role for E2 in inhibiting EMT in humans was suggested in a study which found that reduced expression of ESR1 was associated with increased expression of genes involved in EMT in endometrial carcinoma samples [47]. Further, EMT is a target for sex hormones in cell types such as breast and prostate cancer cells where E2 signaling maintains an epithelial phenotype and suppresses EMT [4851].…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64][65][66] The association between EMT and PI3K activation has also been reported in ERα-negative endometrial carcinomas. [67] Twist overexpression has also been correlated with the induction of tumor cell invasion in GBM. [68] However, these malignancies usually do not metastasize out of the CNS, mainly due to their rapid relapse rate and poor prognosis.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%